UK and Thai Corporate Social Responsibility in the Petrochemical Industry - Siriwattanarungsee, Chatchai (2009)
Corporate Social Responsibility (CSR) has been studied and applied extensively in Western countries since 1950s. CSR is mainly adapted in important businesses such as banking and petrochemical industry. Companies could distribute CSR information towards the public by several means particularly by the internet. Therefore, in this study, analysis of CSR between UK and Thai petrochemical companies based on online CSR disclosure was conducted. The findings are UK companies engage in CSR deeply and intensely more than Thai companies in petrochemical industry.